2016
DOI: 10.1089/dia.2015.0405
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Continuous Glucose Monitoring in Patients After Total Pancreatectomy with Islet Autotransplantation

Abstract: Background: Among postsurgical and critically ill patients, malglycemia is associated with increased complications. Continuous glucose monitoring (CGM) in the inpatient population may enhance glycemic control. CGM reliability may be compromised by postsurgical complications such as edema or vascular changes. We utilized Clarke Error Grid (CEG) and Surveillance Error Grid (SEG) analysis to evaluate CGM performance after total pancreatectomy with islet autotransplantation. Materials and Methods: This subanalysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The investigators found that CGM values had a clinically acceptable correlation with blood glucose values . Forlenza et al . have demonstrated the value of CGM in the total pancreatectomy with IAT adult patient population, using a closed loop system during the transition from insulin infusion to subcutaneous insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators found that CGM values had a clinically acceptable correlation with blood glucose values . Forlenza et al . have demonstrated the value of CGM in the total pancreatectomy with IAT adult patient population, using a closed loop system during the transition from insulin infusion to subcutaneous insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike intermittent monitoring, CGM can provide useful data about the direction of change, the magnitude of change, and warnings to predict hypoglycemia and hyperglycemia occurrences before and after a threshold is reached. There have been several favorable adult reports of CGM use in the ICU setting and one report of its use following IAT in adults . There are limited reports in critically ill children that support CGM usage, and the utility of CGM in the pediatric IAT population in the immediate postoperative setting has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…All other parameters are system determined based on the previous days of total daily insulin and fasting glycemic control. This system has been studied in inpatient, hotel, camp, and outpatient settings with favorable glycemic outcomes (10)(11)(12)(13)(14). The pivotal study of the 670G system involved 124 participants with type 1 diabetes aged 14-75 years wearing the system for 3 months in an outpatient setting.…”
mentioning
confidence: 99%
“…4,5 More recently, other populations such as those with total pancreatectomy with islet autotransplantation (TPIAT) are being studied as reported in this issue of the Journal. 6 Patients with chronic pancreatitis undergoing TPIAT or total pancreatectomy without islet autotransplantation (TP) represent a growing cohort worldwide. Patients enrolled for TPIAT may be euglycemic or have various stages of hyperglycemia from impaired glucose tolerance to diabetes mellitus.…”
mentioning
confidence: 99%
“…15 Forlenza et al report measures of CEG and SEG in their report. 6 They compare CGM data 10 min after YSI measurement with YSI data obtained every 30 min. 16 The seven subjects in their study provide about 21 days of data.…”
mentioning
confidence: 99%